The Impact of Terrorism And Political Events On Stock Market: Empirical Evidence From Pakistan (International Journal of Scientific Research and Management (IJSRM), 2016)
The aim of this paper is to explore the relationship between political & terrorist activities in Pakistan on the stock market development. The paper presents data on the reaction of financial markets to the terrorist attacks and political instability in Pakistan (2011-2014). T-statistic is used to measure the impact of terrorism and political events on stock exchange market. In order to determine the Average return (AR), moving average method is used .The results of the study have shown that Terrorism and Political events negatively affect stock market returns in the short run; whereas there is no significant relationship between stock market returns, Terrorism and Political events in the long run. A potential limitation of the study was the constraint related to the available yearly economic growth and other economic variables’ data. The data for the study was based on the terrorist & political activities for the year 2010 to 2014 on an incident to incident basis. Based on the empirical results, it is being recommended that governments should pay particular attention to economic recovery in the aftermath of terrorist attacks and political unrest and the policies aimed at combating terrorism must be the priority of the government, so that its harm can be reduced, if not exterminated. Political unrest can be addressed through parliament house and judiciary. Terrorism and Political events, with its all kinds of impacts, affect the society and its activities and therefore must be eliminated if an economy needs to prosper. This study envisions the overall impact of terrorist activities and political events, not just as a single activity but also on the health of the economy. For studying this impact, a t-statistics has been used for this study